2011
DOI: 10.1177/000348941112000611
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Cystic Neck Lesions

Abstract: Objectives: In patients less than 40 years of age who present with an upper anterior triangle cystic mass, branchial cyst is the presumed clinical diagnosis. Squamous cell malignancy is the important differential diagnosis in a patient more than 40 years of age. We sought to identify the range of lesions that can be clinically mistaken for, and removed as, branchial cysts. Methods: We performed retrospective reviews of 29 neck masses removed as branchial cysts and 47 solitary neck masses diagnosed as cancer be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 14 publications
1
46
0
5
Order By: Relevance
“…Few previous studies have been carried out in a similar manner; the cohort of the present study is the largest ever reported. Sira et al described 29 patients and found a malignancy rate of 6.9%, while Cinberg et al reported a malignancy rate of 22% in 18 patients . The present findings are consistent with previous studies; however, our data was collected from four different hospitals, thus making them more heterogeneous compared to the studies by Sira et al and Cinberg et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few previous studies have been carried out in a similar manner; the cohort of the present study is the largest ever reported. Sira et al described 29 patients and found a malignancy rate of 6.9%, while Cinberg et al reported a malignancy rate of 22% in 18 patients . The present findings are consistent with previous studies; however, our data was collected from four different hospitals, thus making them more heterogeneous compared to the studies by Sira et al and Cinberg et al…”
Section: Discussionmentioning
confidence: 99%
“…Benign/congenital lateral neck cysts (LNC) are a relatively rare clinical entity, appearing as head and neck masses in children and adults. LNC typically arise from the second branchial arch and most frequently become symptomatic in the second and third decade . Of all cervical tumors, the congenital conditions account for 12%; almost one‐fourth of these represent LNCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients younger than 40 years, clinicians should be aware of a metastasis of a papillary thyroid carcinoma [1]. After a careful history and thorough clinical examination further investigations should include ultrasonography of the neck including FNAC and 3-dimensional imaging either with computed tomography (CT) or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsja jest użytecznym narzędziem diagnostycznym i uznanym standardem postępowania w odniesieniu do guzów litych, gdzie jej swoistość ocenia się na bliską 100%, a odsetek wyników fałszywie negatywnych na mniej niż 3%. W odniesieniu do zmian torbielowatych biopsja cienkoigłowa jest znacznie mniej przydatna, ze względu na bardzo wysoki odsetek wyników fałszywie negatywnych, sięgający 38-63% według różnych badań [12,13]. Nordemar i wsp.…”
Section: Omówienieunclassified